2019
DOI: 10.1093/mnras/stz1809
|View full text |Cite
|
Sign up to set email alerts
|

Radio emission from accreting isolated black holes in our galaxy

Abstract: Apart from the few tens of stellar-mass black holes discovered in binary systems, an order of 10 8 isolated black holes (IBHs) are believed to be lurking in our Galaxy. Although some IBHs are able to accrete matter from the interstellar medium, the accretion flow is usually weak and thus radiatively inefficient, which results in significant material outflow. We study electron acceleration generated by the shock formed between this outflow and the surrounding material, and the subsequent radio synchrotron emiss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…(See [58] and references therein for more details.) Direct measurement of isolated Galactic black holes, such as by radio observations [58,59], would significantly reduce the uncertainties in their properties.…”
Section: A Simulating Positions and Velocitiesmentioning
confidence: 99%
“…(See [58] and references therein for more details.) Direct measurement of isolated Galactic black holes, such as by radio observations [58,59], would significantly reduce the uncertainties in their properties.…”
Section: A Simulating Positions and Velocitiesmentioning
confidence: 99%
“…Fender et al (2013), for instance, found that values larger than λ = 0.01 are excluded, under realistic assumptions, by observations of the local region, where a significant population of isolated BHs should be present. Tsuna et al (2018) and Tsuna & Kawanaka (2019) consider values between λ = 0.1 and λ = 10 −3 . The λ parameter may effectively capture the outflow of material that is expelled from the Bondi sphere, as suggested by several authors (Blandford & Begelman 1999).…”
Section: The Bhl Modelmentioning
confidence: 99%
“…Previous studies (Fender et al 2013;Tsuna et al 2018;Tsuna & Kawanaka 2019) obtained their estimates through Monte Carlo simulations of a BH population. Here, we adopt instead a semianalytical approach that allows us to perform a comprehensive parametric study associated with the physical model of accretion physics described above.…”
Section: E S T I M At I N G T H E N U M B E R O F V I S I B L E S O U R C E Smentioning
confidence: 99%
See 1 more Smart Citation
“…(See [56] and references therein for more details.) Direct observation of isolated Galactic black holes, such as by radio observations [56,57], would significantly reduce the uncertainties in their properties.…”
Section: A Simulating Positions and Velocitiesmentioning
confidence: 99%